101 Ethnic Variation in Hypertrophic Cardiomyopathy. (6th June 2015) - Watkinson, Oliver; Elliott, Perry; Tome, Maite; Guttman, Oliver; O'Mahony, Costas
Abstract : Introduction: Hypertrophic cardiomyopathy (HCM) is a genetic disorder with significant variability in its clinical phenotype. Most major studies in HCM to date have been largely based on Caucasian patients, but there are some indications that racial background may have an important effect on the disease course. In other areas (such as athletes and hypertensive patients) black patients have been shown to be significantly different to white patients in terms of ECG and echocardiographic appearances. In this study we have used a large single centre population to determine the effect of racial group on baseline phenotype and clinical outcomes in HCM. Methods: The case records of sequential patients with hypertrophic cardiomyopathy referred to our cardiomyopathy clinic were reviewed. Patients were asked to identify their racial group using the standard Office of National Statistics classification. Patients who identified themselves as mixed race were excluded. Patients underwent comprehensive cardiac assessment at their baseline visit, and were followed up regularly, for a mean of 7 years. Results: Records were available for 2248 patients (95 Black/African/Caribbean/Black British (B), 216 Asian/Asian British (A), 1937 White (W)). Asian patients were more likely to be male (W 66%, B 66%, A 78%, p < 0.02). At baseline assessment, there were differences in the morphological pattern of left ventricular hypertrophy on echo, with more B patients having apical and concentric distributions of hypertrophy, while W and A patients mostly displayed asymmetric septal hypertrophy (p < 0.02). There were no significant differences between racial groups in terms of maximal wall thickness, fractional shortening and left ventricular outflow tract gradient, but W patients had slightly higher left atrial diameter than other groups at presentation (W 44 mm, B 42 mm, A 42 mm, p 0.02). During follow-up, there were significant differences between ethnic groups in a combined end-point of mortality and cardiac transplant (Annual rates W 1.4%, B 1.7%, A 0.6%, p 0.02), but there were no significant differences in a secondary combined end-point of sudden cardiac death, aborted sudden death, and appropriate ICD therapy (Annual rates W 0.4%, B 0.4%, A 0.2%, p 0.4). W patients were significantly more likely to receive a pacemaker (Annual rates W 1.8%, B 0.9%, A 0.8%, p < 0.02). B patients had a trend to fewer ICDs (Annual rates W 3.5%, B 2.5%, A 4.3% p 0.18). Rates of septal reduction therapy were similar across groups (Annual rates W 3.0%, B 3.1%, A 2.2% p 0.2). Conclusions: In this large single centre study of hypertrophic cardiomyopathy, there were significant differences between racial groups in terms of their clinical phenotype at presentation and their long term outcomes. Further work is required to try and understand the different genetic and social factors which lead to these different disease patterns.